PERAN KOMUNITAS FOTOGRAFI PEKANBARU (KFP) DALAM TRANSFORMASI ILMU FOTOGRAFI - Payoka, Viki; ", Suyanto, (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Communityisafenomenalthinghappeninsociety.Therearemanycommunitieslikephotographycommunity,runnercommunity,bicyclecommunity,automotivecommunityetc.Theachievementofthecommunitydependonthepeopleinit.Forexample,photographycommunitycontainsofagroupofpeoplewholovephotography,interactandsharesameinterestinphotography.ThepurposeofthisresearchistofindouttheachievementofPekanbaruPhotographyCommunity.Howthiscommunitybecomeabigandwell-‐knownforit’sachievement,wetheritisinthegrouporthememberitself.Writerusedqualitativemethod.Dataiscollectedthroughobservation,interviewanddocumentusing.TheachievementofKFPmemberinfluenceinstitutionandbusinesscreativityofphotography.Writerchose17interviewer.Theyareorganizer,observer,sympathizerandKFPmemberwhosuccessfromphotography.Writeralsoattachtheachievementdocumentationofthemember.ResultshowsthatthereisinfluenceofgroupachievementtheoryusedbywriterintoPekanbaruPhotographyCommunityknowledge.Thereiscommunity’sroleintransformingphotographyknowledgetoit’smembersucheducation,seeingthechangethatcangivepositiveimpacttoindividuorgroup.Besides,supportingandbarrierfactorinknowledgetransformingarealsopartofsuccessstoryofthecommunity.Keyword:PekanbaruPhotographyCommunity,Transforming,PhotographyKnowledge